Emerging trends and research foci of neuromyelitis optica spectrum disorder: a 20-year bibliometric analysis - Su, Yue; Ruan, Zhe; Li, Shicao; Li, Zhuyi; Chang, Ting (Frontiers in Immunology, 2023)
Background: Neuromyelitis optica spectrum disorders (NMOSD) is a demyelinating syndrome of the central nervous system. A tremendous amount of literature on NMOSD has been published. This study aimed to perform a bibliometric analysis of the publications on the NMOSD and show its hotspots and development trends. Methods: We used the Web of Science Core Collection as the database and searched the literature published between 2000 and 2022. CiteSpace, VOSviewer, online bibliometric platform, and R-bibliometrix were used to conduct bibliometric analysis and network visualization, including the number of publications, citations, countries/regions, institutions, journals, authors, references, and keywords. Results: A total of 3057 publications on NMOSD were published in 198 journals by 200 authors at 200 institutions from 93 countries/regions. The United States published the most literature and made great contributions to this field. The Mayo Clinic was the institution with the largest number of publications. The journal with the most publications was Multiple Sclerosis and Related Disorders, and the most co-cited journal was Neurology. The author with the most publications was Fujihara, K., while the most frequently co-cited author was Wingerchuk, DM. The current research hotspots may be focused on “efficacy,” “multicenter,” “interleukin-6 receptor blockade,” “safety,” “azathioprine,” “tolerance,” and “adult”. Conclusion: This study was the first bibliometric analysis of publications on NMOSD field and visualized their bibliometric characteristics, and gained insight into the frontiers, hotspots, and development of global NMOSD research, which may provide a helpful information for researchers. The future research hotspots might be conducting randomized controlled trials on targeted immunotherapy in the NMOSD field.